Advancements in thermoelectric materials for efficient waste heat recovery and renewable energy generation - Rakesh Singh; Surya Dogra; Saurav Dixit; Nikolai Ivanovich Vatin; Rajesh Bhardwaj; Ashok K. Sundramoorthy; H.C.S. Perera; Shashikant P. Patole; Rajneesh Kumar Mishra; Sandeep Arya (Hybrid Advances, 2024)
Recent advancements in thermoelectric (TE) materials have opened up new possibilities for efficient waste heat recovery and renewable energy generation. The latest innovations in thermoelectric materials, including novel composites, nanostructured systems, and low-dimensional materials, have significantly enhanced the thermoelectric performance, thereby enabling higher efficiency in waste heat conversion. Integration strategies, such as incorporating thermoelectric modules into industrial exhaust streams, automotive exhausts, and solar thermal collectors, have demonstrated the feasibility and scalability of thermoelectric energy conversion technologies. Moreover, these advancements not only offer a sustainable energy solution but also contribute to reducing greenhouse gas emissions and enhancing overall energy efficiency, aligning with global efforts towards mitigating climate change. Thermoelectric (TE) materials provide an answer by turning excess heat into electricity through the Seebeck effect. It is crucial to have low thermal conductivity (κ) and high thermoelectric power factor (S2σ) when assessing efficiency using the ZT metric. This review explores the latest developments in thermoelectric (TE) materials spanning diverse categories, including the SnSe series, HH alloys, BiTe series, organic-inorganic composites, Cu2Se series, oxides, and GeTe/PbTe series. Through detailed exploration of preparation methods and TE properties for each material, the review offers insights into their potential for efficient waste heat recovery and renewable energy generation. Additionally, it discusses strategies aimed at enhancing the performance of these TE materials, proposing promising avenues for further improving their properties and applicability in sustainable energy technologies.